Creep resistant, low hysteresis, low drift ionic gel thin film, pressure sensor and method of making and use thereof

CN122898079APending Publication Date: 2026-10-13WUTONG SENSATION CONTROL (BEIJING) TECH CO LTD +2
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611400371.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-10
Publication Date
2026-10-13

AI Technical Summary

Technical Problem

[0006]本发明提供了一种抗蠕变、低迟滞、低漂移的离子凝胶薄膜、压力传感器及其制备方法和应用,至少解决了现有技术中传统热塑性聚合物离子凝胶因线性分子链段间相互作用弱而导致的力学迟滞大、回弹性差,以及在离子液体增塑作用下易发生分子链滑移和离子迁移,导致长期负载下材料蠕变严重、几何尺寸改变进而引起电容信号漂移,从而无法满足柔性压力传感器在复杂工况下高稳定性与精准反馈需求的问题

Benefits of technology

本发明通过引入热塑性聚氨酯与原位交联的丙烯酸酯聚合物,构建了半互穿网络结构,其中柔性连续相包含热塑性聚氨酯,刚性分散相包含交联丙烯酸酯聚合物。该微观网络结构有效限制了聚合物分子链在受力形变过程中的滑移运动,在保持薄膜优异柔韧性的同时,显著提升了复合体系的模量与回弹性,克服了传统热塑性离子凝胶因线性分子链相互作用弱而导致的力学迟滞大和应力软化问题。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122898079A_ABST
    Figure CN122898079A_ABST
Patent Text Reader

Abstract

The application discloses an ion gel film with creep resistance, low hysteresis and low drift, and a preparation method and application thereof, and belongs to the technical field of ion gel films. The film raw materials comprise a polymer matrix, an ionic liquid, nano white carbon black modified by a silane coupling agent, a crosslinking system and a solvent. The matrix comprises PVDF, PVDF-HFP and thermoplastic polyurethane; and the crosslinking system is in-situ crosslinked to form an acrylate polymer. The film has a semi-interpenetrating network structure comprising the thermoplastic polyurethane as a flexible continuous phase and the acrylate polymer as a rigid dispersed phase, and the modified white carbon black is coupled with the matrix interface. The semi-interpenetrating network and the interface coupling mechanism constructed by the application effectively limit the molecular chain slip, improve the resilience and reduce the mechanical hysteresis; meanwhile, the modified white carbon black anchors the ionic liquid, prevents the migration and precipitation of the ionic liquid, and overcomes the signal drift problem under long-term load.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of ion gel film technology, specifically relating to an ion gel film with anti-creep, low hysteresis, and low drift, a pressure sensor, its preparation method, and its application. Background Technology

[0002] In recent years, flexible tactile pressure sensing technology has developed rapidly. It not only simulates human tactile perception but also possesses the characteristics of being lightweight, thin, and large. It can achieve tactile sensing capabilities by being applied to the surface of objects, and has significant application value in fields such as the Internet of Things, intelligent robots, wearable electronics, and human-computer interaction. Ionized pressure sensors have attracted widespread attention due to their high sensitivity, high resolution, high signal-to-noise ratio, anti-interference, and static response. Currently, the core sensing material of ionized pressure sensors is usually an ionogel film, which is generally composed of a dissociable salt electrolyte uniformly dispersed within a polymer matrix framework. Common methods for preparing ionogels include dissolving polar polymers and electrolytes in a good solvent and preparing them through solvent evaporation, or pre-dispersing ionic liquids in polymer monomers or prepolymers, binding the ionic liquids within the polymer network during the polymerization and cross-linking process.

[0003] Currently, ionogel films used in ion sensors are mostly made from thermoplastic resins and ionic liquids, with the polymer matrix serving as the polymer backbone and the ionic liquid as the liquid medium. However, thermoplastic polymers are mostly linear molecular structures, resulting in weak interactions between polymer molecular chains during deformation recovery and significant hysteresis. Furthermore, the inherent hysteresis of the polymer's mechanical behavior and the poor compatibility between the molecular chains and the ionic liquid lead to poor elasticity and fatigue resistance in ionogels. Especially after prolonged high-strain compression cycles, ionogels exhibit significant hysteresis and stress softening due to plastic deformation, directly affecting the response time and cyclic reliability of devices fabricated using this ionogel.

[0004] Furthermore, the plasticizing effect of ionic liquids reduces the hardness of thermoplastic polymers and enhances the mobility of molecular chain segments. Under pressure, these polymers are prone to deformation and creep, resulting in excessively tight contact and adhesion with the electrodes. This reduces the sensor's resilience and limits its lifespan. The loose structure of the abundant liquid electrolyte in ionogels leads to increased ion migration and material fluidity under prolonged load, causing significant material creep. This creep alters the geometry of the sensing material, such as thickness changes and dimensional deformation. These geometric changes directly affect the sensor's capacitance measurement principle, causing signal drift and preventing the sensor from providing accurate pressure feedback, significantly reducing its practical application value.

[0005] It should be noted that this part of the present invention only provides background technology related to the present invention, and does not necessarily constitute prior art or known technology. Summary of the Invention

[0006] This invention provides an ion gel film with anti-creep, low hysteresis, and low drift, a pressure sensor, its preparation method, and its application. It at least solves the problems of traditional thermoplastic polymer ion gels in the prior art, which suffer from large mechanical hysteresis and poor resilience due to weak inter-segment interactions between linear molecular chains, and are prone to molecular chain slippage and ion migration under the plasticizing effect of ionic liquids. These problems lead to severe material creep and changes in geometric dimensions under long-term load, resulting in capacitance signal drift, and thus cannot meet the high stability and accurate feedback requirements of flexible pressure sensors under complex working conditions.

[0007] To achieve the above objectives, in a first aspect, the present invention provides an ionomer gel film with anti-creep, low hysteresis, and low drift characteristics. The raw materials, by weight, include: 10-30 parts of a polymer matrix, 5-20 parts of an ionic liquid, 0.5-12 parts of nanofillers, 5-20 parts of a crosslinking system, and 60-80 parts of a solvent. The polymer matrix includes PVDF, PVDF-HFP, and thermoplastic polyurethane. The nanofillers include silane coupling agent-modified nano-fumed silica. The crosslinking system includes crosslinking monomers, a crosslinking agent, and an initiator. The crosslinking monomers undergo in-situ crosslinking under the action of the initiator and the crosslinking agent to form a crosslinked acrylate polymer. The ionomer gel film has a semi-interpenetrating network structure. The semi-interpenetrating network structure includes a flexible continuous phase and a rigid dispersed phase. The flexible continuous phase comprises thermoplastic polyurethane, and the rigid dispersed phase comprises the crosslinked acrylate polymer. The silane coupling agent-modified nano-fumed silica is interfacially coupled with at least one of the thermoplastic polyurethane and the crosslinked acrylate polymer through surface chemical interaction. In the infrared spectrum of the ionomer gel film, at least 3340-3342 cm⁻¹ is included. -1 The characteristic peak of NH stretching vibration at 1725~1728 cm⁻¹ -1 The characteristic peaks of carbonyl C=O at 1529–1531 cm⁻¹ -1 Characteristic peaks of NH bending vibration and CN stretching vibration at the location.

[0008] Preferably, based on the total mass of the polymer matrix, the content of PVDF is 70%~85%, the content of PVDF-HFP is 5%~15%, and the content of thermoplastic polyurethane is 10%~20%; the weight-average molecular weight of PVDF is 800,000~1,000,000, and the molecular weight distribution is 1.8~2.5; the weight-average molecular weight of PVDF-HFP is 100,000~300,000, and the molecular weight distribution is 1.5~2.0.

[0009] Preferably, the thermoplastic polyurethane has a Shore A hardness of 75 to 95, and is selected from at least one of BASF 1180A, BASF 1185A, BASF 1190A, BASF 1195A, Covestro 3680AU, Covestro 3685AU, Covestro 3690AU, and Covestro 3695AU.

[0010] Preferably, the ionic liquid is selected from at least one of 1-ethyl-3-methylimidazolium trifluoromethanesulfonylimide, 1-butyl-3-methylimidazolium di(trifluoromethanesulfonyl)imide, 1-butyl-3-methylimidazolium tetrafluoroborate, 1-butyl-3-methylimidazolium hexafluorophosphate, 3-methyl-1-hexylimidazolium bromide, and 1-ethyl-3-methylimidazolium acetate.

[0011] Preferably, the silane coupling agent is selected from at least one of γ-aminopropyltriethoxysilane, γ-glycidoxypropyltrimethoxysilane, and γ-methacryloyloxypropyltrimethoxysilane.

[0012] Preferably, the nanofiller also includes at least one of nano zinc oxide, nano aluminum oxide, and nano silicon nitride.

[0013] Preferably, based on the total mass of the crosslinking system, the crosslinking monomer accounts for 60% to 80% of the crosslinking system, the crosslinking agent accounts for 15% to 30% of the crosslinking system, and the initiator accounts for 1% to 10% of the crosslinking system; the crosslinking monomer is selected from at least one of methyl methacrylate, ethyl methacrylate, and propyl methacrylate; the crosslinking agent is selected from at least one of trimethylolpropane triacrylate, triallyl isocyanurate, ethylene glycol dimethacrylate, and dicumyl peroxide; and the initiator is selected from at least one of azobisisobutyronitrile, 1,1'-azobiscyclohexanenitrile, and benzoyl peroxide.

[0014] Preferably, the solvent includes a first solvent and a second solvent; the first solvent is N,N-dimethylformamide, N,N-dimethylacetamide or N-methylpyrrolidone, accounting for 70% to 90% of the total solvent mass; the second solvent is dimethyl carbonate, accounting for 10% to 30% of the total solvent mass.

[0015] Preferably, the infrared spectrum of the ionogel film further includes the 1225~1231 cm⁻¹ range. -1 and 1329~1353cm -1 The characteristic peak at 1225~1231 cm -1 The characteristic peak at 1329–1353 cm⁻¹ corresponds to the stretching vibration of the sulfonyl group in the anion of the ionic liquid. -1 The characteristic peak at that location corresponds to the asymmetric contraction vibration of the sulfonyl group in the anion of the ionic liquid.

[0016] Preferably, the infrared spectrum of the ionogel film also includes the 1595~1599 cm⁻¹ range. -1 The characteristic peak at 1595~1599 cm⁻¹ -1 The characteristic peak at that location corresponds to the vibration of the C=C skeleton of the benzene ring in aromatic thermoplastic polyurethane.

[0017] Secondly, the present invention provides a method for preparing an ion gel film according to the first aspect, comprising the following steps: Step S1: Hydrolyze the silane coupling agent in a hydrolysate, add nano-silica to react, wash and dry to obtain silane coupling agent modified nano-silica. Step S2: Dissolve PVDF, PVDF-HFP and thermoplastic polyurethane in a solvent, heat and stir, then stir at room temperature until completely dissolved to obtain a polymer solution; add ionic liquid and silane coupling agent modified nano-silica to the polymer solution, disperse by ultrasonication, let stand at room temperature, then add crosslinking monomer, crosslinking agent and initiator, and stir at room temperature to obtain an ionized solution; Step S3: Coat the ionized solution onto the substrate, heat to evaporate the solvent and dry to form a film, and then bake under vacuum to obtain an ion gel film.

[0018] Preferably, in step S1, the hydrolysate is a mixture of ethanol and water in a volume ratio of (8~9):(2~1), the amount of silane coupling agent added is 5%~10% of the mass of nano-silica, the temperature is raised to 50~70℃ and stirred for 2~3h; the drying is carried out under vacuum at 70~90℃ for 5~7h.

[0019] Preferably, in step S2, the heating and stirring conditions are: oil bath heating and stirring at 80~100℃ for 2~4 hours, stirring at room temperature for 22~26 hours; ultrasonic dispersion time is 5~10 minutes; and stirring at room temperature after adding crosslinking monomer, crosslinking agent and initiator is 10~14 hours.

[0020] Preferably, in step S3, the substrate is a PET film, and the thickness of the wet film formed by coating is 100μm~2000μm; the conditions for drying the film by heating and evaporating the solvent are 70~85℃ for 3~24h; and the conditions for vacuum baking are 70~80℃ for 46~50h.

[0021] Thirdly, the present invention provides a pressure sensor comprising a backing substrate, an ion gel film, and interdigitated electrodes arranged in sequence.

[0022] Fourthly, the present invention provides an application of a pressure sensor in flexible electronic skin, wearable medical devices, human-computer interaction or Internet of Things sensing devices.

[0023] The beneficial effects of this invention are as follows: This invention constructs a semi-interpenetrating network structure by introducing thermoplastic polyurethane and in-situ crosslinked acrylate polymers. The flexible continuous phase comprises thermoplastic polyurethane, while the rigid dispersed phase comprises crosslinked acrylate polymers. This microstructure effectively restricts the slippage of polymer molecular chains during deformation under stress, significantly improving the modulus and resilience of the composite system while maintaining the film's excellent flexibility. This overcomes the problems of large mechanical hysteresis and stress softening caused by weak linear molecular chain interactions in traditional thermoplastic ionogels.

[0024] This invention introduces silane coupling agent-modified nano-silica as the core nanofiller. The silane coupling agent-modified nano-silica undergoes interfacial coupling with at least one of thermoplastic polyurethane and cross-linked acrylate polymers through surface chemical interactions. This interfacial bonding effectively improves the interfacial stress transfer efficiency of the composite material, inhibits the propagation of microcracks, and enhances the creep resistance and dimensional stability of the film. Simultaneously, the high specific surface area of ​​the nano-silica exhibits physical adsorption of ionic liquids, effectively anchoring free ionic liquids and preventing their migration and precipitation under long-term loading, thereby overcoming the capacitance signal drift problem caused by changes in film geometry.

[0025] The preparation process of this invention employs a dual-solvent system in a specific ratio, combining the spontaneous crystallization characteristics of PVDF and PVDF-HFP with the dispersing effect of modified silica to induce a microstructure with micro-nano protrusions and dense porous structure on the film surface. This surface structure provides a compressible volume when the sensor is under pressure, increases the rate of change of the effective contact area between the sensitive layer and the electrode, and improves the sensitivity and signal response resolution of the pressure sensor.

[0026] This invention provides a pressure sensor based on the above-mentioned ion gel film, which has high cyclic reliability and environmental adaptability, exhibits low hysteresis error and signal drift rate under long-term dynamic load, and can accurately reflect pressure changes. It is suitable for fields such as flexible electronic skin, wearable medical devices, human-computer interaction and Internet of Things sensing devices. Attached Figure Description

[0027] To more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings used in the embodiments will be briefly introduced below. It should be understood that the following drawings only show some embodiments of the present invention and should not be regarded as a limitation on the scope. For those skilled in the art, other related drawings can be obtained based on these drawings without creative effort.

[0028] Figure 1 The image shows the FTIR characterization of the ion gel film provided in Example 1 of this invention. Figure 2This is a SEM image of the ion gel film provided in Example 1 of the present invention at a scale of 500 nm. Figure 3 This is a SEM image of the ionogel film provided in Example 1 of the present invention at the 1 μm scale; Figure 4 This is a SEM image of the ionogel film provided in Example 1 of the present invention at a scale of 5 μm. Figure 5 This is a SEM image of the ionogel film provided in Example 1 of the present invention at a scale of 20 μm. Figure 6 Images showing the hysteresis performance test of a pressure sensor fabricated from an ion gel film according to Embodiment 1 of the present invention. Figure 7 This is a 1MPa creep performance test image of a pressure sensor made of an ion gel film provided in Embodiment 1 of the present invention. Figure 8 Images of a pressure sensor made of an ion gel film according to Embodiment 1 of the present invention, showing 1000 full-scale dynamic drift tests. Figure 9 A frontal view schematic diagram of a pressure sensor made of an ion gel film according to Embodiment 1 of the present invention; Figure 10 This is a top-view schematic diagram of a pressure sensor made from an ion gel film according to Embodiment 1 of the present invention. Detailed Implementation

[0029] In this invention, unless otherwise stated, directional terms such as "up," "down," "left," and "right" are generally understood in conjunction with the accompanying drawings and the directions shown in actual applications.

[0030] Furthermore, the terms "first" and "second" are used for descriptive purposes only and should not be construed as indicating or implying relative importance or implicitly specifying the number of technical features indicated. Thus, a feature defined as "first" or "second" may explicitly or implicitly include one or more of that feature. In the description of this invention, "a plurality of" means two or more, unless otherwise explicitly specified.

[0031] In this invention, unless otherwise explicitly specified and limited, "above" or "below" the second feature can mean that the first feature is in direct contact with the second feature, or that the first feature is in indirect contact with the second feature through an intermediate medium. Furthermore, "above," "over," and "on top" of the second feature can mean that the first feature is directly above or diagonally above the second feature, or simply that the first feature is at a higher horizontal level than the second feature. "Below," "below," and "under" the second feature can mean that the first feature is directly below or diagonally below the second feature, or simply that the first feature is at a lower horizontal level than the second feature.

[0032] The endpoints and any values ​​of the ranges disclosed herein are not limited to the precise ranges or values, and should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of the various ranges, the endpoint values ​​of the various ranges and individual point values, and individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein. The terms "optional" and "discretionary" mean that they may or may not be included (or may or may not be present).

[0033] In a first aspect, the present invention provides an ion gel film with anti-creep, low hysteresis, and low drift. The raw materials for preparation include, by weight, 10 to 30 parts of polymer matrix, which can be 10 parts, 12 parts, 15 parts, 18 parts, 20 parts, 22 parts, 25 parts, 28 parts, 30 parts, and any value between them. The ionic liquid is 5 to 20 parts, which can be 5, 8, 10, 12, 15, 18, 20 parts, or any value between them; The nanofiller is 0.5 to 12 parts, and can be 0.5 parts, 1 part, 3 parts, 5 parts, 7 parts, 9 parts, 11 parts, 12 parts and any value between them; The crosslinking system consists of 5 to 20 parts, which can be 5, 8, 10, 12, 15, 18, 20 parts, or any value between them; The solvent is 60 to 80 parts, which can be 60, 65, 70, 75, 80 parts or any value in between.

[0034] The polymer matrix includes PVDF (polyvinylidene fluoride), PVDF-HFP (polyvinylidene fluoride-hexafluoropropylene copolymer), and thermoplastic polyurethane (TPU). Nanofillers include silane coupling agent-modified nano-silica; The crosslinking system includes crosslinking monomers, crosslinking agents, and initiators. The crosslinking monomers crosslink in situ under the action of initiators and crosslinking agents to form crosslinked acrylate polymers. The ion gel film has a semi-interpenetrating network structure; the semi-interpenetrating network structure includes a flexible continuous phase and a rigid dispersed phase; the flexible continuous phase includes thermoplastic polyurethane, and the rigid dispersed phase includes cross-linked acrylate polymer; the silane coupling agent modified nano-silica is interfacially coupled with at least one of the thermoplastic polyurethane and cross-linked acrylate polymer through surface chemical interaction. The infrared spectrum of the ionogel film contains at least the 3340~3342 cm⁻¹. -1 The characteristic peak of NH stretching vibration at 1725~1728 cm⁻¹ -1 The characteristic peaks of carbonyl C=O at 1529–1531 cm⁻¹ -1 Characteristic peaks of NH bending vibration and CN stretching vibration at the location.

[0035] In this invention, the semi-interpenetrating network structure refers to a multiphase composite structure formed by at least one linear or branched polymer chain and at least one three-dimensional cross-linked polymer network interpenetrating and topologically entangled at the molecular scale. Unlike a fully interpenetrating network structure (i.e., two cross-linked networks interpenetrate each other), in a semi-interpenetrating network structure, only one side is a chemically cross-linked three-dimensional network, and the other side is an uncross-linked linear or branched molecular chain; the two are spatially interpenetrating and interlocked, but each maintains chemical independence, that is, no covalent cross-linking bonds are formed between the linear polymer chain and the cross-linked network.

[0036] In the ionogel film of the present invention, the semi-interpenetrating network structure is specifically manifested as a composite system of a flexible continuous phase and a rigid dispersed phase. The flexible continuous phase is the phase that forms a continuous matrix in the film, endowing the material with flexibility, elastic recovery ability, and compatibility with ionic liquids. The flexible continuous phase includes thermoplastic polyurethane, and also includes PVDF and PVDF-HFP as the basic dielectric framework. Among them, the thermoplastic polyurethane has a linear molecular structure, and its molecular chains are composed of alternating hard and soft segments. The hard segments form physically cross-linked microdomains through hydrogen bonding and π-π stacking, while the soft segments provide conformational deformation ability. PVDF and PVDF-HFP are both linear thermoplastic polymers, which dissolve and intertwine with the thermoplastic polyurethane in the solution blending stage, and together they constitute the continuous phase matrix. The flexible continuous phase is continuously distributed in the film and is the main channel phase for ionic liquid storage and ion migration. The rigid dispersed phase is a cross-linked polymer phase distributed in a dispersed form in the flexible continuous phase. Its storage modulus is significantly higher than that of the flexible continuous phase, and it plays a rigid supporting and confining role. The rigid dispersed phase comprises a cross-linked acrylate polymer formed by in-situ free radical polymerization and cross-linking of cross-linking monomers within a flexible continuous phase under the action of a cross-linking agent and an initiator. It exhibits thermosetting characteristics, with its molecular chains linked by covalent cross-linking bonds into an irreversible three-dimensional structure, macroscopically manifesting as a high-modulus, high-rigidity supporting framework.

[0037] Understandably, the three-dimensional network of cross-linked acrylate polymers grows in situ within a continuous phase matrix composed of linear molecular chains of thermoplastic polyurethane and fluoropolymers. The linear molecular chains penetrate the pores of the cross-linked network, and the chain segments of the cross-linked network are also entangled between the linear molecular chains, forming a topological interlock at the microscale. Since there are no covalent bonds between the linear molecular chains in the flexible continuous phase and the cross-linked network in the rigid dispersed phase, they cooperate only through physical entanglement and topological interlock. Therefore, this structure is a semi-interpenetrating network structure, not a fully interpenetrating network structure. In this semi-interpenetrating network structure, the cross-linked acrylate network of the rigid dispersed phase acts as a high-modulus rigid support node, effectively restricting the large-scale slippage of the thermoplastic polyurethane and fluoropolymer molecular chains in the flexible continuous phase during deformation under stress. After stress removal, the cross-linked network, through the elastic restoring force of the covalent cross-links, pulls the restricted linear molecular chains back to their initial conformation, thereby maintaining the film's flexibility while improving the storage modulus and resilience of the composite system and reducing mechanical hysteresis.

[0038] Understandably, in the face of the problems of large mechanical hysteresis and poor resilience caused by weak inter-segment interactions between linear molecular chains in traditional thermoplastic polymer ionogels, as well as severe material creep and signal drift caused by ionic liquid migration under long-term load, this invention provides a new solution by constructing a multi-scale synergistic semi-interpenetrating network structure and interface coupling mechanism.

[0039] Conventional thermoplastic elastomers, when subjected to tensile or compressive forces, exhibit irreversible slippage between their linear molecular chains, failing to quickly return to their initial state after the force is removed, thus displaying significant mechanical hysteresis on a macroscopic scale. To overcome this deficiency, this invention employs polyvinylidene fluoride (PVDF) and PVDF-hexafluoropropylene copolymer as the basic dielectric framework in the polymer matrix design. PVDF's high crystallinity provides mechanical support and a high dielectric constant, while the lower crystallinity of the PVDF-hexafluoropropylene copolymer enhances the system's flexibility and compatibility with ionic liquids. Furthermore, this invention abandons a single linear network design, introducing a crosslinking system capable of in-situ polymerization. Within a flexible continuous phase blended with thermoplastic polyurethane and fluoropolymers, a three-dimensional network of crosslinked acrylate polymers is interwoven as a rigid dispersed phase. In this semi-interpenetrating network structure, the flexible continuous phase comprises thermoplastic polyurethane, and the rigid dispersed phase comprises crosslinked acrylate polymers, achieving topological entanglement and anchoring at the microscopic level. When the ionogel film is subjected to deformation stress, the cross-linked acrylate polymer network, as a high-modulus rigid support point, can effectively restrict the large-scale slippage of the thermoplastic polyurethane and fluoropolymer molecular chains. After the stress is removed, the molecular chains are forcibly pulled back to their original position by the restoring force of the chemical cross-linking bonds. Thus, while maintaining the excellent flexibility of the film, the energy storage modulus of the composite system is greatly improved and the mechanical hysteresis is reduced.

[0040] In suppressing material creep and signal drift, this invention innovatively introduces silane coupling agent-modified nano-silica as a core nanofiller, which functions through chemical coupling and physical adsorption. At the interfacial coupling level, the surface of the silane coupling agent-modified nano-silica has active functional groups, which can form interfacial bonds with at least one of thermoplastic polyurethane and cross-linked acrylate polymers through surface chemical interactions. Specifically, when the silane coupling agent is γ-methacryloyloxypropyltrimethoxysilane containing unsaturated double bonds (such as KH570), its double bonds can participate in the free radical polymerization reaction of olefinic monomers, forming covalent bonds between modified silica and crosslinked acrylate polymers; when the silane coupling agent is γ-glycidoxypropyltrimethoxysilane containing epoxy groups (such as KH560), its epoxy groups can undergo ring-opening reactions with the active hydrogen in the polyurethane hard segment under appropriate conditions to form chemical bonds; when the silane coupling agent is γ-aminopropyltriethoxysilane containing amino groups (such as KH550), the silanol groups formed after hydrolysis condense with the hydroxyl groups on the surface of nano-silica to form siloxane bonds, and the amino groups can form hydrogen bonds and dipole interactions with the urethane groups and ester groups in the polyurethane hard segment. The aforementioned surface chemical effects significantly enhance the stress transfer efficiency at the interface between the inorganic nanofiller and the organic phase, enabling uniform dissipation of external loads and preventing the generation and propagation of microcracks. This strengthens the dimensional stability and creep resistance of the film from a mechanical structural perspective. At the physical adsorption level, the high specific surface area of ​​the nano-silica can also effectively anchor ionic liquids through surface silanol groups and modified groups, effectively resisting the plasticizing effect of ionic liquids on the polymer matrix. This prevents macroscopic migration or precipitation of ionic liquids under prolonged extrusion or high-frequency dynamic loading, eliminating changes in film geometry caused by material rheology and ion migration, thereby resolving the long-term drift defect of the pressure sensor's capacitive signal.

[0041] Regarding the proportions of each component, this invention establishes a synergistic balance range among them. Using 10-30 parts of polymer matrix ensures the basic mechanical strength of the film after formation. 5-20 parts of ionic liquid provide the necessary ionic conductivity for the film, imparting ionization sensing properties to the material. This dosage range also ensures that the ionic liquid is sufficiently bound within the adsorption sites of the semi-interpenetrating network and nano-fumed silica, preventing excessive free ionic liquid from exacerbating plasticization creep of the matrix. The crosslinking system is controlled within 5-20 parts to ensure that the formed rigid dispersed phase has sufficient crosslinking density to suppress creep, while avoiding excessive crosslinking that could lead to loss of overall material flexibility, brittle fracture, or hinder the uniform dispersion of the ionic liquid.

[0042] Characteristic peaks in the infrared spectrum were used to characterize and confirm the successful construction of the composite structure, particularly the formation of the semi-interpenetrating network and interfacial coupling mechanism. The NH stretching and bending vibration peaks confirmed the presence of hydrogen bonds in the hard segments of the polyurethane, while the peaks at 1725–1728 cm⁻¹...-1 The C=O characteristic peak at the point is the result of the superposition and combined effect of the ester carbonyl group in the cross-linked acrylate polymer and the urethane carbonyl group in the polyurethane. The appearance of this superposition peak proves that the rigid acrylate network and the flexible polyurethane matrix have undergone close interweaving and interaction at the molecular scale, indicating the successful construction of the semi-interpenetrating network structure.

[0043] Understandably, the above infrared spectroscopy tests were performed using an attenuated total reflectance Fourier transform infrared spectrometer (ATR-FTIR) equipped with a diamond ATR crystal. Specific test conditions were as follows: the ionogel film was cut into samples approximately 1 cm × 1 cm, and the tests were conducted at room temperature and a relative humidity not exceeding 60%; the scanning range was 4000–400 cm⁻¹. -1 The resolution is 4cm. -1 The number of scans was 32; at least three different locations were selected for testing each sample, and the average spectrum was used as the infrared spectrum of the sample.

[0044] Preferably, based on the total mass of the polymer matrix, the PVDF content is 70% to 85%, and can be 70%, 72%, 75%, 78%, 80%, 82%, 85%, and any value between them; The PVDF-HFP content is 5%~15%, and can be 5%, 7%, 9%, 10%, 12%, 14%, 15% and any value between them; The content of thermoplastic polyurethane is 10% to 20%, and can be 10%, 12%, 14%, 16%, 18%, 20%, or any value between them.

[0045] The weight-average molecular weight of PVDF is 800,000 to 1,000,000, which can be 800,000, 850,000, 900,000, 950,000, 1,000,000 and any value between them. The molecular weight distribution is 1.8 to 2.5, which can be 1.8, 1.9, 2.0, 2.1, 2.2, 2.3, 2.4, 2.5 and any value between them.

[0046] The weight-average molecular weight of PVDF-HFP is 100,000 to 300,000, which can be 100,000, 150,000, 200,000, 250,000, 300,000 and any value between them. The molecular weight distribution is 1.5 to 2.0, which can be 1.5, 1.6, 1.7, 1.8, 1.9, 2.0 and any value between them.

[0047] Understandably, in the specific composition design of the polymer matrix, the selection of a blend system of three specific polymer materials is to achieve a balance between mechanical toughness, creep resistance, and ion transport performance. PVDF, as the main component of the matrix, is set at a proportion of 70% to 85%, providing a stable polymer backbone for the entire ionogel network. PVDF molecular chains contain a large number of strongly polar CF bonds, which can coordinate with ionic liquids through ion-dipole interactions, contributing to the uniform dispersion of ionic liquids in the matrix and promoting the dissociation of ion pairs. The selection of PVDF with a weight-average molecular weight of 800,000 to 1,000,000 is to utilize the dense physical entanglement between the ultra-long molecular chains to impart excellent tear strength and fatigue fracture resistance to the film. The molecular weight distribution is controlled within the range of 1.8 to 2.5 to avoid unnecessary long-term slow creep of the material caused by low molecular weight grades acting as internal plasticizers. The introduction of PVDF-HFP is to regulate the crystallinity of the matrix. The steric hindrance effect of the asymmetric groups of hexafluoropropylene (HFP) can break the original regular chain segment arrangement of PVDF, reduce the crystalline region of the polymer, and increase the free volume of the amorphous region. The amorphous region is the main channel for ionic liquid storage and ion migration. Therefore, 5%~15% PVDF-HFP can significantly improve the response sensitivity and ionic conductivity of the ionization sensor. The weight-average molecular weight of this component is set at 100,000~300,000. Its relatively low molecular weight allows it to act as a flexible connecting bridge in the PVDF polymer chain network, improving the processing rheological properties of the blend system. Thermoplastic polyurethane, as the third component, is controlled at 10%~20%. It mainly utilizes its microphase separation structure (composed of hard and soft segments) to give the film excellent elastic recovery. Under compressive deformation, the soft segments of polyurethane undergo conformational expansion to absorb energy, while the hard segments act as physical crosslinking points to maintain network integrity; after stress relief, the soft segments spontaneously curl up to provide rebound force. The synergistic effect of the three polymers in a specific ratio gives the matrix both the chemical stability and polarity of fluoropolymers and the elasticity of polyurethane. Combined with the aforementioned cross-linked acrylate rigid network, this helps to solve the problem of plastic deformation of the sensing film under dynamic loads and ensures high fidelity of the sensor output signal.

[0048] Optionally, the Shore A hardness of the thermoplastic polyurethane is 75 to 95, and can be 75, 78, 80, 82, 85, 88, 90, 92, 95 and any value between them, selected from at least one of BASF 1180A, BASF 1185A, BASF 1190A, BASF 1195A, Covestro 3680AU, Covestro 3685AU, Covestro 3690AU and Covestro 3695AU.

[0049] Understandably, controlling the hardness of thermoplastic polyurethane helps achieve low hysteresis performance. Shore A hardness is an important indicator characterizing the ability of elastomer materials to resist localized plastic deformation. It is usually measured using a Shore hardness tester under standard ambient temperature and test conditions by the depth to which an indenter penetrates the sample surface. If the hardness of thermoplastic polyurethane is too low, the material tends to undergo larger plastic deformation, increasing the risk of creep under long-term load; if the hardness is too high, the film flexibility decreases, the deformation capacity under small pressure is reduced, and it may affect the sensitivity of the sensor. Selecting thermoplastic polyurethane with a hardness of 75~95A ensures that the material possesses ideal elasticity and modulus, while also having a highly optimized hard / soft segment microphase separation microstructure. This structure allows the hard segment microregions to act as physical anchors to uniformly transfer stress when the material is under load, while the soft segment regions provide conformational deformation without hysteresis. The present invention can use the above-mentioned optional thermoplastic polyurethane, which has excellent weather resistance, hydrolysis resistance and compatibility with fluoropolymers, and can ensure that it is uniformly dissolved in the solvent system. After drying and forming a film, it forms a macroscopically uniform and microscopically multiphase synergistic composite structure with the PVDF matrix and acrylate network, thereby providing highly stable and repeatable mechanical response characteristics.

[0050] Preferably, the ionic liquid is selected from at least one of 1-ethyl-3-methylimidazolium trifluoromethanesulfonylimide (EMIM-TFSI), 1-butyl-3-methylimidazolium di(trifluoromethanesulfonyl)imide (BMIM-TFSI), 1-butyl-3-methylimidazolium tetrafluoroborate (BMIM-BF4), 1-butyl-3-methylimidazolium hexafluorophosphate (BMIM-PF6), 3-methyl-1-hexylimidazolium bromide ([HMIM]Br), and 1-ethyl-3-methylimidazolium acetate ([EMIM]Ac).

[0051] Preferably, the silane coupling agent is selected from at least one of γ-aminopropyltriethoxysilane (KH550), γ-glycidoxypropyltrimethoxysilane (KH560), and γ-methacryloyloxypropyltrimethoxysilane (KH570).

[0052] Preferably, the nanofiller also includes at least one of nano zinc oxide, nano aluminum oxide, and nano silicon nitride.

[0053] Understandably, ionic liquids, as conductive and sensitive components of flexible pressure sensing films, possess excellent ionic conductivity and good fluidity, ensuring good compatibility with the polymer matrix. The preferred imidazole ionic liquids in this application have anions such as trifluoromethanesulfonylimide, which exhibit strong hydrophobicity and chemical inertness, effectively reducing the film's tendency to adsorb environmental moisture and ensuring electrochemical stability. The alkyl side chains on their cations provide steric hindrance, further reducing the ionic liquid's affinity for water molecules. The choice of silane coupling agent depends on the reactivity of its functional groups with the polymer matrix. The amino groups generated after the hydrolysis of γ-aminopropyltriethoxysilane can form hydrogen bonds and dipole interactions with the urethane or ester groups in polyurethane, enhancing interfacial bonding. The epoxy groups of γ-glycidoxypropyltrimethoxysilane can undergo ring-opening reactions with the active hydrogens in polyurethane under appropriate conditions. The double bonds of γ-methacryloyloxypropyltrimethoxysilane can directly participate in the in-situ crosslinking reaction of acrylates, thereby constructing a robust chemical interface between the inorganic filler and the organic matrix. The introduction of auxiliary nanofillers such as nano zinc oxide, nano aluminum oxide, and nano silicon nitride can not only adjust the dielectric constant of the film, but also provide additional physical crosslinking points in the polymer matrix, improve the thermal conductivity of the composite system, and prevent the performance degradation of the sensor due to local heat accumulation under high-frequency dynamic load.

[0054] Preferably, based on the total mass of the crosslinking system, the crosslinking monomer accounts for 60% to 80% of the crosslinking system, and can be 60%, 65%, 70%, 72%, 75%, 78%, 80%, and any value between them; The crosslinking agent accounts for 15% to 30% of the crosslinking system, and can be 15%, 18%, 20%, 22%, 25%, 28%, 30%, or any value between them; The initiator accounts for 1% to 10% of the crosslinking system, and can be 1%, 2%, 4%, 6%, 8%, 10%, or any value between them.

[0055] Preferably, the crosslinking monomer is selected from at least one of methyl methacrylate (MMA), ethyl methacrylate (EMA), and propyl methacrylate (PMA).

[0056] Preferably, the crosslinking agent is selected from at least one of trimethylolpropane triacrylate (TMPTA), triallyl isocyanurate (TAIC), ethylene glycol dimethacrylate (EGDMA), and dicumyl peroxide (DCP).

[0057] Preferably, the initiator is selected from at least one of azobisisobutyronitrile (AIBN), 1,1'-azobiscyclohexanenitrile (ACCN), and benzoyl peroxide (BPO).

[0058] Understandably, controlling the composition and ratio of the crosslinking system is to construct a rigid dispersed phase with ideal crosslinking density at the microscale. The crosslinking monomers are dominant (60%–80%), and the selected methacrylic acid monomers (such as methyl methacrylate) can form hard polymer segments with glass transition temperatures much higher than room temperature after polymerization. These hard segments can support the rigidity of the entire polymer backbone in the ionogel system. If the monomer ratio is less than 60%, the resulting rigid segments are too short to form an effective supporting phase; if it is higher than 80%, the distance between crosslinking points will be too long, resulting in an insufficiently dense network. 15%–30% of the crosslinking agent is responsible for connecting these linear hard segments into a three-dimensional network. A multifunctional crosslinking agent containing three polymerizable double bonds, such as trimethylolpropane triacrylate (TMPTA), is selected. Its star-shaped molecular structure can couple in three spatial directions, forming extremely high-density crosslinking nodes. This high-density network structure allows external stress to be rapidly dissipated throughout the network system via cross-linking bonds. Once the external force disappears, the strong internal stress within the cross-linked network instantly forces the system to rebound, thus endowing the film with excellent low hysteresis properties. Controlling the initiator concentration within the range of 1% to 10% determines the rate of free radical generation and the half-life of the polymerization reaction. The selection of thermal initiators such as azobisisobutyronitrile (AIBN) ensures that its decomposition temperature perfectly matches the subsequent solvent evaporation and drying temperature window, guaranteeing a uniform distribution of the rigid dispersed phase within the flexible continuous phase.

[0059] Preferably, the solvent includes a first solvent and a second solvent; the first solvent is N,N-dimethylformamide (DMF), N,N-dimethylacetamide (DMAC) or N-methylpyrrolidone (NMP), accounting for 70% to 90% of the total mass of the solvent; the second solvent is dimethyl carbonate (DMC), accounting for 10% to 30% of the total mass of the solvent.

[0060] Understandably, the dual-solvent system of this invention not only achieves efficient dissolution of each component but also facilitates the subsequent spontaneous formation of microscopic surface structures. The first solvent (such as N,N-dimethylformamide DMF), as a strongly polar aprotic solvent, dominates (70%~90%). Its high boiling point and excellent solubility can break the crystalline entanglement between PVDF molecular chains and completely extend and solubilize the hard and soft segments of the thermoplastic polyurethane, ensuring a homogeneous and stable solution in the initial stage of preparation. The addition of the second solvent, dimethyl carbonate (DMC), is controlled at 10%~30%, with a relatively low boiling point and rapid evaporation rate. This combination of solvents with different boiling points induces a significant gradient evaporation effect during the coating and drying film-forming stage. In the initial stage of film formation, the second solvent DMC in the surface layer rapidly evaporates, causing a sharp increase in the local concentration of the polymer solution, triggering thermodynamic instability and phase transformation (i.e., spontaneous microphase separation). This phase separation mechanism induced by solvent non-equilibrium evaporation, combined with the spontaneous crystallization behavior of PVDF, forms numerous micro- and nano-scale protrusions and dense porous microstructures on the film surface. When a small pressure is applied, the surface protrusions readily undergo compressive deformation, displacing air at the interface and significantly increasing the effective contact area with the electrode, thereby generating a huge capacitance change and endowing the sensor with extremely high pressure resolution and sensitivity. Furthermore, the high content of the first solvent ensures that the main structure of the film has sufficient time for molecular chain rearrangement and in-situ cross-linking and solidification, guaranteeing the overall density and mechanical strength of the ionogel and avoiding macroscopic cracking or internal stress warping defects caused by excessively rapid solvent evaporation.

[0061] Preferably, the infrared spectrum of the ionogel film further includes the 1225~1231 cm⁻¹ range. -1 and 1329~1353cm -1 The characteristic peak at 1225~1231 cm -1 The characteristic peak at 1329–1353 cm⁻¹ corresponds to the stretching vibration of the sulfonyl group in the anion of the ionic liquid. -1 The characteristic peak at that location corresponds to the asymmetric contraction vibration of the sulfonyl group in the anion of the ionic liquid.

[0062] Preferably, the infrared spectrum of the ionogel film also includes the 1595~1599 cm⁻¹ range. -1 The characteristic peak at 1595~1599 cm⁻¹ -1 The characteristic peak at that location corresponds to the vibration of the C=C skeleton of the benzene ring in aromatic thermoplastic polyurethane.

[0063] Understandably, these infrared spectral characteristic peaks can verify the stability and compatibility of the multiphase composite system constructed in this invention at the microscopic molecular level. The stretching vibration and asymmetric contraction vibration characteristic peaks of the sulfonyl group (-SO2-) in the ionic liquid appear in the above-mentioned frequency band, and the absorption peaks are sharp without abnormal broadening or shift, which can prove that the anion (such as TFSI) - The ionic liquid exists in a free, highly active state within the gel matrix, free from severe aggregation or chemical degradation. This indicates a good physical encapsulation and weak charge interaction between the polymer matrix and the ionic liquid. The ionic liquid's structure is not destroyed by the cross-linking reaction, thus ensuring the system's excellent ionic conductivity and dielectric response to pressure. Simultaneously, the ionic liquid exhibits a high electrical conductivity of 1595–1599 cm⁻¹. -1 The clear presentation of the C=C skeletal vibration peaks of the aromatic thermoplastic polyurethane confirms that the hard segments of the polyurethane maintain the integrity of their molecular skeleton even after undergoing a complex process involving solvent dissolution, ultrasonic dispersion, and high-temperature crosslinking. The presence of aromatic hard segments enables the formation of physical crosslinking centers through a strong π-π stacking effect and hydrogen bond network, which complements the chemical crosslinking network of acrylates generated by in-situ polymerization. Physical crosslinking points can reversibly break down to dissipate impact energy during initial deformation, while chemical crosslinking points prevent permanent deformation.

[0064] Secondly, the present invention provides a method for preparing an ion gel film according to the first aspect, comprising the following steps: Step S1: Hydrolyze the silane coupling agent in a hydrolysate, add nano-silica to react, wash and dry to obtain silane coupling agent modified nano-silica. Step S2: Dissolve PVDF, PVDF-HFP and thermoplastic polyurethane in a solvent, heat and stir, then stir at room temperature until completely dissolved to obtain a polymer solution; add ionic liquid and silane coupling agent modified nano-silica to the polymer solution, disperse by ultrasonication, let stand at room temperature, then add crosslinking monomer, crosslinking agent and initiator, and stir at room temperature to obtain an ionized solution; Step S3: Coat the ionized solution onto the substrate, heat to evaporate the solvent and dry to form a film, and then bake under vacuum to obtain an ion gel film.

[0065] Understandably, the present invention provides a preferred preparation method that organically combines surface modification, solution blending and in-situ crosslinking technology through specific process steps to ensure the consistency of the microstructure and macroscopic properties of the final ionogel film.

[0066] In step S1, the pre-hydrolysis of the silane coupling agent converts the alkoxy groups of the coupling agent molecules into highly reactive silanol groups. These silanol groups can undergo condensation dehydration reactions with the endogenous hydroxyl groups on the surface of the nano-fumed silica to form strong siloxane covalent bonds, thereby grafting organic tails with specific reactive or compatible groups onto the surface of inorganic particles. This step effectively reduces the surface free energy of the fumed silica, preventing the agglomeration and sedimentation of nanoparticles in the subsequent polymer solution. The order of feeding and operating conditions in step S2 determine the rheological stability and network uniformity of the mixed system. First, the three polymers are completely dissolved by heating and stirring to untangle the physical entanglement of the macromolecular chains and form a viscous, continuous, homogeneous solution. Then, the ionic liquid and modified nano-fumed silica are added and ultrasonically dispersed. The viscous resistance of the polymer solution itself is used to transfer the ultrasonic shear force, which can completely break up the fumed silica agglomerates and allow the ionic liquid molecules to diffuse uniformly into the amorphous regions of the polymer. In addition, the crosslinking system (monomer, crosslinking agent, and initiator) is added last after the system has been allowed to stand and cool to room temperature. This is to prevent premature thermal decomposition of the initiator during early heating or high-energy ultrasonic shearing, which could lead to localized explosive polymerization of the acrylate. Room temperature stirring ensures that the crosslinking components achieve uniform molecular-level dispersion without any reaction. In step S3, the post-coating heating and drying not only removes the solvent to bring the polymer macromolecular chains closer together and create entanglement, but also activates the decomposition of the initiator at the set heating temperature, initiating the free radical polymerization of the crosslinking monomers. This simultaneous solvent evaporation and shaping, along with the growth of the chemical crosslinking network, further contributes to the formation of a semi-interpenetrating structure where the thermoplastic polyurethane continuous phase and the rigidly dispersed crosslinked acrylate phase intertwine. The subsequent vacuum baking process is responsible for deeply removing trace amounts of solvent remaining inside the crosslinking network, preventing it from plasticizing and weakening the material's creep resistance, and preventing its continued evaporation from causing electrical property drift.

[0067] Preferably, in step S1, the hydrolysate is a mixture of ethanol and water with a volume ratio of 8:2, 8.5:1.5, or 9:1; the amount of silane coupling agent added is 5%, 6%, 7%, 8%, 9%, 10% of the mass of nano-silica, or any value between them; the temperature is raised to 50°C, 55°C, 60°C, 65°C, 70°C, or any value between them; the reaction is stirred for 2 hours, 2.5 hours, 3 hours, or any value between them; and the drying is carried out at 70°C, 75°C, 80°C, 85°C, 90°C, or any value between them; the drying is carried out under vacuum for 5 hours, 5.5 hours, 6 hours, 6.5 hours, 7 hours, or any value between them.

[0068] In step S2, the heating and stirring conditions are 80℃, 85℃, 90℃, 95℃, 100℃ and any value between them; oil bath heating and stirring for 2h, 3h, 4h and any value between them; room temperature stirring time for 22h, 23h, 24h, 25h, 26h and any value between them; ultrasonic dispersion time for 5min, 6min, 7min, 8min, 9min, 10min and any value between them; and room temperature stirring time after adding crosslinking monomer, crosslinking agent and initiator for 10h, 11h, 12h, 13h, 14h and any value between them.

[0069] In step S3, the substrate is a PET film, and the thickness of the wet film formed by coating is 100μm, 200μm, 500μm, 1000μm, 1500μm, 2000μm and any value between them; the conditions for heating and evaporating the solvent to dry the film are 70℃, 75℃, 80℃, 85℃ and any value between them for 3h, 6h, 12h, 18h, 24h and any value between them; the conditions for vacuum baking are 70℃, 75℃, 80℃ and any value between them for 46h, 47h, 48h, 49h, 50h and any value between them.

[0070] Understandably, the pH value of the hydrolysate and the reaction temperature in step S1 determine the hydrolysis rate and grafting rate of the silane coupling agent. A specific ratio of ethanol to water provides a suitable polar environment, and the temperature range of 50–70°C ensures the full progress of the hydrolysis reaction while preventing the self-polymerization of the silane coupling agent. Controlling the amount of silane coupling agent added to 5%–10% ensures the formation of a dense monolayer modification on the surface of the silica; excessive addition leads to residual free coupling agent, affecting the electrical properties of the film. In step S2, oil bath heating and stirring at 80–100°C ensures the complete dissolution of the high-viscosity fluoropolymer and the full extension of the molecular chains. Subsequent 22–26 hours of room temperature stirring eliminates the concentration gradient within the system. Controlling the ultrasonic dispersion time helps to break up the hard agglomerates of silica while avoiding excessive ultrasonication that could lead to polymer chain degradation. 10–14 hours of room temperature stirring provides sufficient kinetic time for the in-situ crosslinking reaction, ensuring the integrity of the network structure. In step S3, the control of the wet film thickness affects the final film's microstructure development and solvent removal efficiency. Heating at 70-85°C causes the low-boiling-point co-solvent to evaporate preferentially, inducing the formation of surface micro- and nano-structures. Subsequent vacuum baking completely removes the high-boiling-point main solvent, avoiding film stickiness and mechanical property degradation caused by solvent residue, and ensuring the film's low creep and low drift characteristics under long-term load.

[0071] Thirdly, the present invention provides a pressure sensor comprising a backing substrate, an ion gel film, and interdigitated electrodes arranged in sequence.

[0072] Understandably, the pressure sensor provided in this application employs an asymmetric AB layered structure. The backing substrate, serving as the underlying support, is typically made of flexible insulating material, such as polyethylene terephthalate film or polyimide film. The main function of the backing substrate is to provide necessary macroscopic mechanical support for the internally ionically conductive sensitive layer, ensuring the integrity of the overall structure when subjected to bending, torsion, or shear stress, and preventing tearing or damage to the sensitive ion gel film. Interdigitated electrodes are disposed on the other side of the ion gel film, their alternating finger-like structures creating a symmetrical edge electric field. Under the influence of the electric field, the anions and cations within the ion gel film are directionally enriched at the electrode interface, forming a stable double-layer capacitance structure. Because the ion gel film of this application incorporates a semi-interpenetrating network structure and modified nanofillers, it possesses extremely low mechanical hysteresis and creep resistance. The change in the effective contact area with the interdigitated electrodes under pressure can accurately and reversibly reflect the magnitude of the external pressure. After the external load is unloaded, the film can quickly recover its initial microstructure without signal baseline drift caused by residual plastic deformation. In addition, the tight adhesion between the backing substrate and the ionogel film eliminates interfacial voids and avoids additional parasitic capacitance introduced by the interfacial air layer, ensuring high fidelity and long-term reliability of the sensor's capacitive signal.

[0073] Preferably, the thickness of the backing substrate is controlled within the range of 10μm to 300μm. Limiting the thickness of the backing substrate within this range ensures, on the one hand, that the substrate has sufficient mechanical strength and dimensional stability, preventing wrinkling or excessive stretching deformation of the film during assembly or actual attachment, thereby ensuring uniform transmission of external stress to the ionogel film; on the other hand, this thickness range allows the sensor to maintain excellent overall flexibility, enabling it to closely conform to human skin or various complex curved surfaces, avoiding stress shielding effects or signal distortion caused by poor adhesion due to excessive substrate thickness.

[0074] Fourthly, the present invention provides an application of a pressure sensor in flexible electronic skin, wearable medical devices, human-computer interaction or Internet of Things sensing devices.

[0075] Understandably, the pressure sensor provided by this invention exhibits significant technical advantages in the aforementioned cutting-edge application fields. In wearable medical device applications (such as non-invasive continuous blood pressure monitors or pulse wave monitoring wristbands), the sensor needs to be tightly attached to the human skin for extended periods, enduring static pre-tension forces caused by the tension of the strap. For traditional gel sensors, this long-term static load leads to severe creep flow in the material, causing the gel thickness to gradually decrease, resulting in continuous and uncontrollable drift of the sensor's baseline capacitance, directly causing distortion or even complete failure of physiological signal extraction. The ionogel of this invention, benefiting from the semi-interpenetrating network structure coupled with silane-modified silica, possesses excellent creep resistance and dimensional stability, ensuring long-term high stability of the reference signal under continuous external force, thus guaranteeing the reliability of medical-grade parameter monitoring. In flexible electronic skin, human-computer interaction scenarios (such as haptic feedback arrays in intelligent robotic hands or VR gloves), and IoT sensing devices, the sensor needs to respond instantaneously to high-frequency dynamic movements and maintain signal consistency during repeated cycles. The sensor’s low hysteresis and high resilience characteristics ensure that it can achieve zero-delay stress response and signal recovery, respond quickly and accurately to minute pressure changes, and maintain excellent cyclic reliability under extreme environments or high-frequency dynamic loads.

[0076] The present invention will be further described in detail below through specific embodiments, but the scope of protection of the present invention is not limited to the following embodiments.

[0077] Example 1 This embodiment provides a creep-resistant, low-hysteresis, and low-drift ion gel film and a method for preparing the pressure sensor thereof. The sensor includes interdigitated electrodes, an ion gel film, and a backing substrate arranged sequentially.

[0078] The raw materials of the ionogel film include the following components by weight: 15 parts PVDF, 2 parts PVDF-HFP, 3 parts thermoplastic polyurethane PU-1185A, 5 parts ionic liquid EMIM-TFSI, 0.5 parts nano alumina, 2 parts fumed silica, 0.2 parts silane coupling agent KH550, 8 parts crosslinking monomer MMA, 2 parts crosslinking agent TMPTA, 0.5 parts initiator AIBN, 60 parts first solvent NMP, and 10 parts second solvent DMC.

[0079] The preparation method of the above-mentioned ionogel film includes the following steps: S1. Preparation of modified silica: Ethanol and water were mixed at a volume ratio of 9:1 to prepare a hydrolyzed silane solution. Then, 0.2 parts of silane coupling agent KH550 were added, and the mixture was magnetically stirred for 30 min to promote complete hydrolysis of the silane. Two parts of fumed silica were added, and the mixture was ultrasonically dispersed for 30 min. The temperature was raised to 60℃, and the mixture was stirred for 2.5 h. The silica dispersion was then filtered and washed three times with anhydrous ethanol to remove unreacted silane. The silica was then vacuum dried at 80℃ for 6 h to obtain silane coupling agent modified silica, which was then sealed for later use.

[0080] S2. Preparation of the ionized solution: 15 parts of polymer PVDF, 2 parts of PVDF-HFP, and 3 parts of PU-1185A were dissolved in a mixed solvent of NMP and DMC at a mass ratio of 60:10. The solution was stirred for 3 hours under oil bath heating at 90°C, followed by stirring at room temperature for 24 hours to ensure complete dissolution of the polymer into a transparent solution. Then, 5 parts of ionic liquid EMIM-TFSI, 2 parts of modified silica, and 0.5 parts of nano-alumina were added, and the solution was ultrasonically broken up for 8 minutes to ensure uniform dispersion of the nanofillers. The solution was then allowed to stand at room temperature, and 8 parts of polymer monomer MMA, 2 parts of crosslinking agent TMPTA, and 0.5 parts of initiator AIBN were added. The solution was stirred at room temperature for 12 hours to promote dispersion and in-situ polymerization of the crosslinking system, thus obtaining the ionized solution.

[0081] S3. Ionized film coating: The ionized solution is evenly coated onto a clean and smooth 50μm thick PET film surface that has been wiped with anhydrous ethanol using a coating machine. The wet film thickness is controlled at 800μm. The film is placed on a water platform in an oven and heated at 80℃ for 12h. After the solvent has completely evaporated and the film has dried, it is placed in a vacuum oven and vacuum baked at 80℃ for 48h. The film is then stored for later use to obtain the ion gel film.

[0082] The assembly method of the above-mentioned ion gel film pressure sensor includes the following steps: using a ring-shaped double-sided adhesive to assemble the ion gel film with a PET backing substrate and the interdigitated electrodes face to face to form an AB structure sensor. The outer layer of the PET backing is encapsulated and protected with PI tape for subsequent application testing.

[0083] Example 2 The only difference between this embodiment and Embodiment 1 is that the type of thermoplastic polyurethane, the type of ionic liquid, and the ratio of the crosslinking system have been adjusted.

[0084] The specific raw material ratio is as follows: 15 parts PVDF, 2 parts PVDF-HFP, 4 parts thermoplastic polyurethane PU-1190A, 8 parts ionic liquid BMIM-TFSI, 0.5 parts nano alumina, 2 parts fumed silica, 0.2 parts silane coupling agent KH550, 12 parts crosslinking monomer MMA, 3 parts crosslinking agent TMPTA, 0.3 parts initiator AIBN, 60 parts first solvent NMP, and 10 parts second solvent DMC.

[0085] The preparation method and sensor assembly method are the same as those in Example 1.

[0086] Example 3 The only difference between this embodiment and Example 1 is that the type of silane coupling agent and the type of crosslinking monomer have been replaced, and the ratio of nanofillers has been adjusted.

[0087] The specific raw material ratio is as follows: 15 parts PVDF, 2 parts PVDF-HFP, 3 parts thermoplastic polyurethane PU-1185A, 5 parts ionic liquid EMIM-TFSI, 2 parts nano alumina, 3 parts fumed silica, 0.3 parts silane coupling agent KH560, 8 parts crosslinking monomer EMA, 2 parts crosslinking agent EGDMA, 0.2 parts initiator AIBN, 60 parts first solvent NMP, and 10 parts second solvent DMC.

[0088] The preparation method and sensor assembly method are the same as those in Example 1.

[0089] Example 4 The only difference between this embodiment and Example 1 is that the proportions of each component in the polymer matrix and the ratio of the dual solvent system have been adjusted.

[0090] The specific raw material ratio is as follows: 16 parts PVDF, 2 parts PVDF-HFP, 2 parts thermoplastic polyurethane PU-1185A, 10 parts ionic liquid EMIM-TFSI, 0.5 parts nano alumina, 1.5 parts fumed silica, 0.15 parts silane coupling agent KH570, 6 parts crosslinking monomer MMA, 1.5 parts crosslinking agent TMPTA, 0.5 parts initiator AIBN, 50 parts first solvent NMP, and 20 parts second solvent DMC.

[0091] The preparation method and sensor assembly method are the same as those in Example 1.

[0092] Comparative Example 1 The only difference between this comparative example and Example 1 is that thermoplastic polyurethane PU-1185A is not added to the raw material formulation; the other raw material types, amounts and preparation steps are the same as in Example 1.

[0093] Comparative Example 2 The only difference between this comparative example and Example 1 is that fumed silica and silane coupling agent KH550 are not added to the raw material formulation, i.e., silane coupling agent modified silica is not prepared; the other raw material types, amounts and preparation steps are the same as in Example 1.

[0094] Test case Hysteresis, 1MPa creep and 1000 full-scale dynamic drift performance tests were conducted on the ion gel thin film pressure sensors prepared in Examples 1 to 4 and Comparative Examples 1 and 2 of this application.

[0095] Hysteresis test method: Pressure is applied using a pressure source device in a stepped pressure mode: 0 MPa, 0.2 MPa, 0.4 MPa, 0.6 MPa, 0.8 MPa, 1 MPa, 1 MPa, 0.8 MPa, 0.6 MPa, 0.4 MPa, 0.2 MPa, 0 MPa. Each step lasts 30 seconds, constituting one cycle. Three consecutive cycles are performed, collecting force and electrical signal data. Within the specified range, at the same test point, the hysteresis error percentage is calculated using the absolute value of the difference in output when the measured value increases and decreases.

[0096] Creep test method: A pressure source device is used to apply pressure. The pressure application mode is as follows: first, the output under no pressure is collected, and then a full-scale pressure of 1 MPa is applied after 1 minute. The pressure is held for 1 hour, and force data and electrical signal data are collected. The percentage of the maximum signal difference value to the initial full-scale output value is calculated over the entire test cycle.

[0097] Full-scale dynamic drift test method: A pressure source device is used to apply pressure. The test mode starts from zero pressure, applies continuous force to the expected range, and then continuously reduces the pressure from the expected range back to zero pressure. This process constitutes one cycle, with a cycle period of 40 seconds. 1000 cycles are performed continuously, and force data and electrical signal data are collected. The percentage of the maximum difference in full-scale output value to the initial full-scale output value is calculated throughout the entire test cycle.

[0098] Test Results The test data for each embodiment and comparative example are shown in Table 1.

[0099] Table 1

[0100] As shown in Table 1, Examples 1 to 4 all fall within the formulation range and process parameters provided by this invention. By constructing a semi-interpenetrating network structure with thermoplastic polyurethane as the flexible continuous phase and crosslinked acrylate polymer as the rigid dispersed phase, and combining the interfacial coupling and physical adsorption effects of silane coupling agent-modified silica, they all exhibit excellent anti-creep, low hysteresis, and low drift properties. Among them, Example 1 shows the best overall performance. Example 2, by adjusting the polyurethane type and crosslinking density; Example 3, by replacing the silane coupling agent and crosslinking monomer types; and Example 4, by adjusting the matrix ratio and dual solvent ratio, all showed slight fluctuations in their test data, but remained at extremely low levels, fully demonstrating the broad applicability and process tolerance of the technical solution of this invention.

[0101] Compared to Example 1, Comparative Example 1, which did not add thermoplastic polyurethane, lost the elastic buffering and high resilience properties of the flexible continuous phase inside the film. Due to the lack of interfacial coupling between the polyurethane molecular chain segments and the modified silica, the molecular chains of the composite material are prone to irreversible slippage under stress, causing its hysteresis error to rise sharply to 15.0%. Furthermore, after losing the thermoplastic polyurethane elastomer, which has good compatibility with ionic liquids, the creep rate at 1 MPa and the full drift rate after 1000 cycles also deteriorated to 18.0% and 16.0%, respectively, failing to meet the basic requirements for the use of flexible pressure sensors.

[0102] Compared to Example 1, Comparative Example 2 did not add fumed silica and silane coupling agent, and the film lacked the physical anchoring effect and surface chemical interface coupling effect of high specific surface area nanofillers. Although the semi-interpenetrating network structure still existed, causing its hysteresis error to increase slightly to 10%, the film geometry changed significantly during pressure holding and cyclic loading because it could not effectively limit the migration and precipitation of ionic liquids under long-term high-frequency loading. This resulted in a significant increase in its creep rate at 1 MPa to 14.0% and a full drift rate of 15.0% after 1000 cycles.

[0103] The technical effects of the present invention will be further explained below with reference to specific experimental results and accompanying drawings.

[0104] Figure 1 The Fourier transform infrared spectrum characterization of the ionogel film provided in Embodiment 1 of the present invention is shown in the figure. At 3341 cm⁻¹... -1 The characteristic peak of NH stretching vibration appeared at 2870 to 3020 cm⁻¹. -1 The characteristic peak of CH stretching vibration appeared at 1530 cm⁻¹. -1 Characteristic peaks of NH bending vibration and CN stretching vibration appeared at 1597 cm⁻¹. -1 The presence of characteristic peaks representing the C=C skeletal vibration of the benzene ring at 701 cm⁻¹ confirms the successful introduction of thermoplastic polyurethane into the film material. -1and 740 cm -1 A SNS symmetrical stretching vibration peak appeared at 837 cm⁻¹. -1 A CF3 bending vibration peak appeared at 1332 cm⁻¹. -1 and 1350 cm -1 A peak of sulfonyl asymmetric contraction vibration appeared at 1228 cm⁻¹. -1 A sulfonyl stretching vibration peak appeared at 1725 cm⁻¹, confirming the successful introduction and uniform dispersion of the ionic liquid in the film. -1 The characteristic peak appearing at 1000-1250 cm⁻¹ is attributed to the combined effect of the ester carbonyl groups in the crosslinked acrylate polymer and the urethane carbonyl groups in the polyurethane. The appearance of this superimposed peak demonstrates the close interweaving of the rigid acrylate network and the flexible polyurethane matrix at the molecular scale, providing spectroscopic evidence of a semi-interpenetrating network structure. Due to the high concentration of ionic liquid and the strong absorption of the fluorinated polymer matrix in the system, the peak value is high from 1000 to 1250 cm⁻¹. -1 The characteristic peaks of silicon-oxygen bonds in the region overlap and mask each other, but the surface chemical interface coupling effect of modified silica can be indirectly verified through the improvement of macroscopic mechanical properties and sensing properties.

[0105] Figures 2-5 The images show the microstructure of the ionogel film provided in Example 1 of this invention under scanning electron microscopy at different magnifications. As shown, due to the difference in evaporation rates between the high-boiling-point and low-boiling-point solvents in the dual-solvent system, and the co-crystallization effect of polyvinylidene fluoride (PVDF) and PVDF-hexafluoropropylene copolymer, the film surface forms a morphology with micro / nano protrusions and a dense porous structure. At the 20 μm and 5 μm scales, uniformly distributed micro / nano protrusion structures can be observed on the surface; further local magnification at the 1 μm and 500 nm scales reveals highly uniform branched and interwoven textures on the protrusion surface. The formation of this microstructure is attributed to the coupling effect of modified silica, which not only forms interfacial bonds with at least one of fluorinated polymers, polyurethanes, and acrylate polymers, promoting the uniform development of the surface micro / nano structure, but also ensures the uniform dispersion and low agglomeration effect of the nanofiller in the matrix due to its strong physical adsorption with the ionic liquid. This surface micro-nano porous structure provides a compressible volume when the sensor is under pressure, increasing the rate of change of the effective contact area between the sensitive layer and the electrode, thereby endowing the thin film with excellent sensing sensitivity.

[0106] Figure 6The figure shows the hysteresis performance test curves of the pressure sensor fabricated from the ionogel film provided in Embodiment 1 of this invention. As shown, during the step-by-step pressurization and depressurization process, the loading curve and unloading curve highly overlap, and the area enclosed by the hysteresis loop is small. This indicates that the sensor exhibits extremely low mechanical hysteresis error during stress deformation and recovery, and can quickly recover to its initial state after unloading without significant residual plastic deformation. These test results confirm that the semi-interpenetrating network structure and interfacial coupling mechanism constructed in this invention can effectively restrict the slippage of polymer molecular chains, endowing the film with excellent high resilience and low hysteresis characteristics.

[0107] Figure 7 The figure shows the 1MPa creep performance test curve of the pressure sensor made from the ionogel film provided in Example 1 of this invention. As shown in the figure, during the test period of applying a constant pressure of 1MPa and maintaining it for 1 hour, the sensor output signal quickly reaches a stable plateau, and the signal fluctuation is minimal throughout the pressure holding phase, with no obvious creep drift phenomenon that decays over time. This result demonstrates the effective physical anchoring effect of modified silica on ionic liquids and the limiting effect of the semi-interpenetrating network structure on molecular chain slippage, enabling the film to maintain excellent dimensional stability under long-term static load, overcoming the technical defect of traditional ionogel films being prone to creep.

[0108] Figure 8 The figure shows the full-scale dynamic drift test curves of the pressure sensor fabricated from the ionogel film provided in Embodiment 1 of this invention after 1000 cycles. As shown, during 1000 consecutive rapid cyclic loading cycles from zero pressure to the expected range and back to zero pressure, the sensor's full-scale output signal remained highly consistent, with extremely high overlap of the cyclic curves and a very low percentage difference between the maximum difference value and the initial full-scale output value. This result conclusively demonstrates that the ionogel film provided by this invention possesses excellent cyclic reliability and anti-signal drift capability under long-term high-frequency dynamic loads, meeting the application requirements for accurate and stable pressure feedback in complex working environments.

[0109] Figure 9 and Figure 10 These are front and top views of the pressure sensor fabricated from the ion gel film provided in Embodiment 1 of the present invention. As shown, the pressure sensor adopts an asymmetric stacked structure, comprising, from top to bottom, a backing substrate, an ion gel film, and interdigitated electrodes. The backing substrate serves as the bottom support, providing macroscopic mechanical support and dimensional stability for the internal sensitive layer; the interdigitated electrodes are disposed below the ion gel film, and their alternating finger-like structures create a symmetrical edge electric field; the ion gel film forms a stable double-layer capacitor structure under the action of the electric field. The tight adhesion between the backing substrate and the ion gel film eliminates interface voids, avoiding additional parasitic capacitance introduced by the interface air layer, and ensuring high fidelity and long-term reliability of the sensor's capacitive signal.

[0110] The preferred embodiments of the present invention have been described in detail above; however, the present invention is not limited thereto. Within the scope of the inventive concept, various simple modifications can be made to the technical solutions of the present invention, including combinations of various technical features in any other suitable manner. These simple modifications and combinations should also be considered as the content disclosed in the present invention and are all within the protection scope of the present invention.

Claims

1. An ionogel film with anti-creep, low hysteresis, and low drift characteristics, characterized in that, The raw materials for preparation, by weight, include: 10-30 parts of polymer matrix, 5-20 parts of ionic liquid, 0.5-12 parts of nanofiller, 5-20 parts of crosslinking system and 60-80 parts of solvent; The polymer matrix includes PVDF, PVDF-HFP, and thermoplastic polyurethane; the nanofiller includes silane coupling agent modified nano-silica; the crosslinking system includes crosslinking monomers, crosslinking agents, and initiators, wherein the crosslinking monomers are crosslinked in situ under the action of the initiator and crosslinking agent to form crosslinked acrylate polymers; The ionogel film has a semi-interpenetrating network structure; the semi-interpenetrating network structure includes a flexible continuous phase and a rigid dispersed phase; the flexible continuous phase includes the thermoplastic polyurethane, and the rigid dispersed phase includes the cross-linked acrylate polymer; the silane coupling agent modified nano-silica is interfacially coupled to at least one of the thermoplastic polyurethane and the cross-linked acrylate polymer through surface chemical interaction. The infrared spectrum of the ionogel film contains at least the 3340~3342 cm⁻¹ region. -1 The characteristic peak of NH stretching vibration at 1725~1728 cm⁻¹ -1 The characteristic peaks of carbonyl C=O at 1529–1531 cm⁻¹ -1 Characteristic peaks of NH bending vibration and CN stretching vibration at the location.

2. The ionogel film according to claim 1, characterized in that, Based on the total mass of the polymer matrix, the PVDF content is 70%~85%, the PVDF-HFP content is 5%~15%, and the thermoplastic polyurethane content is 10%~20%. The PVDF has a weight-average molecular weight of 800,000 to 1,000,000 and a molecular weight distribution of 1.8 to 2.

5. The PVDF-HFP has a weight-average molecular weight of 100,000 to 300,000 and a molecular weight distribution of 1.5 to 2.

0. The thermoplastic polyurethane has a Shore A hardness of 75 to 95, and is selected from at least one of BASF 1180A, BASF 1185A, BASF 1190A, BASF 1195A, Covestro 3680AU, Covestro 3685AU, Covestro 3690AU, and Covestro 3695AU.

3. The ionogel film according to claim 1, characterized in that, The ionic liquid is selected from at least one of 1-ethyl-3-methylimidazolium trifluoromethanesulfonylimide, 1-butyl-3-methylimidazolium di(trifluoromethanesulfonyl)imide, 1-butyl-3-methylimidazolium tetrafluoroborate, 1-butyl-3-methylimidazolium hexafluorophosphate, 3-methyl-1-hexylimidazolium bromide, and 1-ethyl-3-methylimidazolium acetate. The silane coupling agent is selected from at least one of γ-aminopropyltriethoxysilane, γ-glycidoxypropyltrimethoxysilane, and γ-methacryloxypropyltrimethoxysilane. The nanofiller also includes at least one of nano zinc oxide, nano aluminum oxide, and nano silicon nitride.

4. The ionogel film according to claim 1, characterized in that, Based on the total mass of the crosslinking system, the crosslinking monomer accounts for 60% to 80% of the crosslinking system, the crosslinking agent accounts for 15% to 30% of the crosslinking system, and the initiator accounts for 1% to 10% of the crosslinking system; The crosslinking monomer is selected from at least one of methyl methacrylate, ethyl methacrylate, and propyl methacrylate; The crosslinking agent is selected from at least one of trimethylolpropane triacrylate, triallyl isocyanurate, ethylene glycol dimethacrylate, and dicumyl peroxide; The initiator is selected from at least one of azobisisobutyronitrile, 1,1'-azobiscyclohexanenitrile, and benzoyl peroxide.

5. The ionogel film according to claim 1, characterized in that, The solvent includes a first solvent and a second solvent; The first solvent is N,N-dimethylformamide, N,N-dimethylacetamide, or N-methylpyrrolidone, accounting for 70% to 90% of the total mass of the solvent; The second solvent is dimethyl carbonate, accounting for 10% to 30% of the total mass of the solvent.

6. The ionogel film according to claim 1, characterized in that, The infrared spectrum of the ionogel film also includes the range of 1225-1231 cm⁻¹. -1 and 1329~1353 cm -1 The characteristic peak at 1225~1231 cm⁻¹ -1 The characteristic peak at 1329–1353 cm⁻¹ corresponds to the stretching vibration of the sulfonyl group in the ionic liquid anion. -1 The characteristic peak at that location corresponds to the asymmetric contraction vibration of the sulfonyl group in the anion of the ionic liquid; And / or, also includes 1595~1599 cm -1 The characteristic peak at 1595~1599 cm⁻¹ -1 The characteristic peak at that location corresponds to the vibration of the C=C skeleton of the benzene ring in aromatic thermoplastic polyurethane.

7. A method for preparing an ionogel thin film as described in any one of claims 1 to 6, characterized in that, Includes the following steps: Step S1: Hydrolyze the silane coupling agent in a hydrolysate, add nano-silica to react, wash and dry to obtain silane coupling agent modified nano-silica. Step S2: Dissolve PVDF, PVDF-HFP and thermoplastic polyurethane in a solvent, heat and stir, then stir at room temperature until completely dissolved to obtain a polymer solution; add ionic liquid and silane coupling agent modified nano-silica to the polymer solution, disperse by ultrasonication, let stand at room temperature, then add crosslinking monomer, crosslinking agent and initiator, and stir at room temperature to obtain an ionized solution; Step S3: Coat the ionized solution onto the substrate, heat to evaporate the solvent and dry to form a film, and then bake under vacuum to obtain the ion gel film.

8. The method for preparing an ionogel film according to claim 7, characterized in that, In step S1, the hydrolysate is a mixture of ethanol and water in a volume ratio of (8~9):(2~1), the amount of silane coupling agent added is 5%~10% of the mass of nano-silica, the temperature is raised to 50~70℃ and stirred for 2~3h; the drying is vacuum drying at 70~90℃ for 5~7h. In step S2, the heating and stirring conditions are: oil bath heating and stirring at 80~100℃ for 2~4 hours; room temperature stirring time is 22~26 hours; ultrasonic dispersion time is 5~10 minutes; and room temperature stirring time after adding crosslinking monomer, crosslinking agent and initiator is 10~14 hours. In step S3, the substrate is a PET film, and the thickness of the wet film formed by coating is 100μm~2000μm; the conditions for drying the film by heating and evaporating the solvent are 70~85℃ for 3~24h; the conditions for vacuum baking are 70~80℃ for 46~50h.

9. A pressure sensor, characterized in that, It includes a backing substrate, an ion gel film as described in any one of claims 1 to 6, and interdigitated electrodes arranged in sequence.

10. The application of the pressure sensor as described in claim 9 in flexible electronic skin, wearable medical devices, human-computer interaction or Internet of Things sensing devices.